Arabidopsis clade IV TGA transcription factors, TGA10 and TGA9, are involved in ROS-mediated responses to bacterial PAMP flg22. (November 2016) - Noshi, Masahiro; Mori, Daisuke; Tanabe, Noriaki; Maruta, Takanori; Shigeoka, Shigeru
Highlights: Arabidopsis knockout mutants lacking TGA10 exhibit flg22-sensitive phenotype. Expression of TGA10 is induced by flg22 treatment in leaves. Chloroplastic ROS are involved in the flg22-induced TGA10 expression. TGA10 is essential for full activation of the expression of flg22-responsive genes. TGA9 has a minor contribution to flg22 response. Abstract: Reactive oxygen species (ROS) produced in chloroplasts have been proposed to act as signaling molecules for plant immunity through pathogen-associated molecular patterns (PAMPs), such as flg22. To elucidate this process, we herein conducted genetic screening of flg22-sensitive mutants from T-DNA insertion lines lacking chloroplastic H2 O2 -responsive genes. The results obtained showed that knockout mutants lacking a clade IV TGA transcription factor, TGA10, were more sensitive to the flg22 treatment than wild-type plants. Furthermore, although no flg22-sensitive phenotype was detected in the knockout mutant of another clade IV TGA9, double knockout tga9 tga10 mutants showed more sensitivity to flg22 than single knockout mutants. Transcripts of TGA10 and TGA9 were strongly induced by flg22 in leaves, and this was facilitated by the double knockout of stromal and thylakoid-bound ascorbate peroxidases (APX), which are major H2 O2 scavengers in chloroplasts. The flg22-induced H2 O2 accumulation was maintained at high level in these APXs mutants, indicating the clade IV TGAs may be induced by the ROS. Furthermore, TGA10 was required for the complete activation of the expression of several flg22-responsive genes in plants treated with this PAMP. These have provided a new insight into the relationship between the TGA transcription factors and ROS-mediated signaling in PAMPs responses.